Stabilitas Pilar Beton Pracetak Segmental Pada Jembatan Standar Terhadap Beban Dinamik - Anton Husen Purboyo; Hinawan Teguh Santoso (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
The use of precast technology in the manufacture of segmental components for the bridge substructure is one application that can be used in the acceleration of bridge construction. Better concrete quality and precision are two advantages that can make precast technology a solution in accelerating bridge construction. Commonly, segmental precast concrete piers are not designed to resist earthquake loads; however, the use of segmental piers systems is still possible in seismic zones by limiting additional dead loads. This study discusses the load limitation using the dynamic response calculation methodology of segmental precast concrete pillar structures to the El Centro (1940) earthquake load by varying the slenderness of the piers/column between 22 to 100. Examination of the stress combination due to axial load (DL) and inertia load due to the earthquake is carried out to find out how much residual stress can be accommodated by the piers/columns. Additional dead load (WADD) is obtained by using Newton's second law by dividing the allowable additional inertial load based on the residual stress to the peak ground acceleration. The calculation results show a good correlation between piers’/columns’ slenderness and the proportion of additional dead load (WADD) to dead load (WDL), so that the applicability of using segmental precast concrete piers/columns in seismic zones can be predicted earlier through this correlation.